Enhancement of Glutamate Release by l-Fucose Changes Effects of Glutamate Receptor Antagonists on Long-Term Potentiation in the Rat Hippocampus - Matthies, Henry (Cold Spring Harbor Laboratory Press, 2000)
In previous studies l-fucose has been shown to facilitate long-term memory formation and to enhance and prolong long-term potentiation (LTP). To search for possible presynaptic or postsynaptic mechanisms that are affected by l-fucose, we examined the effect of l-fucose on (1) inhibition of LTP induction via glutamate receptors by antagonists, (2) paired-pulse facilitation, and (3) presynaptic transmitter release. Coapplication of 0.2 mm l-fucose with the competitive N-methyl-d-aspartate (NMDA) receptor antagonist, d-2-amino-5-phosphonovalerate (AP5), or coapplication of 0.2 mml-fucose in the presence of an inhibitor for class I/II metabotropic glutamate receptors, (S)-α-methyl-4-carboxyphenylglycine (MCPG), reversed LTP blockade in the CA1-region of hippocampal slices. In contrast, l-fucose had no effect on the LTP blockade by the noncompetitive NMDA ion-channel blocker (5R,10S)-(+)-5-Methyl-10,11-dihydro-5H-dibenzo[a,d]cyclohepten-5, 10-imine hydrogen maleate (MK-801). Paired-pulse facilitation, which is a primarily presynaptic phenomenon of short-term plasticity, was decreased in the presence of 0.2 mm l-fucose. Furthermore, l-fucose enhanced the K(+)-stimulated release of [(3)H]-d-aspartate from preloaded hippocampal slices in a concentration-dependent manner. These observations demonstrate an influence of l-fucose on transmitter release that in turn can increase transmitter availability at postsynaptic glutamate receptors. This effect of l-fucose may contribute to the LTP facilitation seen in vitro and in vivo as well as to improvement in memory formation.